Caractéristiques sociodémographiques des minorités visibles - MRC Vaudreuil-Soulanges - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de MRC Vaudreuil-Soulanges.

Caractéristiques sociodémographiques des minorités visibles - RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de la Montérégie-Ouest.

Socio-Demographic Characteristics of Visible Minorities in MRC de Vaudreuil-Soulanges - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for MRC de Vaudreuil-Soulanges.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Montérégie-Ouest.

August & September 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)

June & July 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)

February & March 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)

2023 Report : "An Analysis of the Demographic and Socio-Economic Characteristics of Quebec's English-Speaking Community Compared to the French-Speaking Population" with a Focus on the RTS de la Montérégie-Oues - Montérégie West Community Network (MWCN) (2023)

Annual Report : 2022-2023 - Montérégie West Community Network (MWCN) (2023)

Demographic Profiles of Québec's English-speaking Communities RTS de la Montérégie-Ouest - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

December 2022 & January 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)

September 2022 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)

July & August 2022 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)

March 2022 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)

Directory of Lawyers, Accountants, Notaries, & Real Estate : 2nd Edition - Cyr, Cathy; Wright, Tonya; Dade, Samantha (2022)

Annual Report 2021-2022 - Montérégie West Community Network (MWCN) (2022)

Monteregie West Healthcare Information Booklet for English Speakers - Montérégie West Community Network (MWCN) (2022)

Booklet for Young Workers : Everything you Need to Know for your First Job - Montérégie West Community Network (MWCN); Educaloi (2022)

Marvelous Monday - Montérégie West Community Network (MWCN) (2021)

Chateauguay / Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2021)

Chateauguay / Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2021)

Vaudeuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2021)

Marvelous Monday - Montérégie West Community Network (MWCN) (2021)

Chateauguay / Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2021)

Vaudeuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2021)

Welcome to Whacky Wednesday - Montérégie West Community Network (MWCN) (2021)

Chateauguay / Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2021)

Vaudeuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2021)

Chateauguay / Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2021)

Vaudeuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2021)

Chateauguay / Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2021)

Vaudeuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2021)

[Dashboards - Quebec and RTS Territories] - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Montérégie-Ouest - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

Chateauguay / Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)

Vaudeuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)

Chateauguay / Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)

Vaudeuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)

Chateauguay/Chateaguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)

Chateauguay/Chateauguay Valley Community Matters - Montérégie West Community Network (MWCN) (2020)

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)

Chateauguay/The Valley Community Matters - Montérégie West Community Network (MWCN) (2020)

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)

Chateauguay Community Matters - Montérégie West Community Network (MWCN) (2020)

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2020)

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2019)

Community Matters - Montérégie West Community Network (MWCN) (2019)

Community Matters - Montérégie West Community Network (MWCN) (2019)

Community Matters - Montérégie West Community Network (MWCN) (2019)

Community Matters - Montérégie West Community Network (MWCN) (2019)

Community Matters - Montérégie West Community Network (MWCN) (2019)

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2019)

Community Matters - Montérégie West Community Network (MWCN) (2019)

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2019)

Community Matters - Montérégie West Community Network (MWCN) (2019)

Vaudreuil-Soulanges Community Matters - Montérégie West Community Network (MWCN) (2019)

Community Matters - Montérégie West Community Network (MWCN) (2018)

Community Matters - Montérégie West Community Network (MWCN) (2018)

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Le Haut-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Vaudreuil-Soulanges - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Community Matters - Montérégie West Community Network (MWCN) (2018)

Community Matters - Montérégie West Community Network (MWCN) (2017)

Community Matters - Montérégie West Community Network (MWCN) (2017)

Community Matters - Montérégie West Community Network (MWCN) (2017)

Community Matters - Montérégie West Community Network (MWCN) (2017)
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest (1630) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest & RLS de Jardins-Roussillon (1634) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest & RLS de Vaudreuil-Soulanges (1631) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest & RLS du Haut-Saint-Laurent (1633) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest & RLS du Suroît - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Children 0 to 5 and their Parents : RTS de la Montérégie-Ouest - Community Health and Social Services Network (CHSSN) (2016)

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Vaudreuil Soulanges (1612) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS du Haut Saint Laurent (1602) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS du Suroit (1603) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Conserving History Through Generations : Vignettes of the Valley - Chateauguay Valley Regional High School

Monteregie West Healthcare Information Booklet - Montérégie West Community Network (MWCN)

Conserving History Through Generations : Building Bridges Over Time - St-Willibrord Elementary School